PENGARUH WAKTU PEMERAMAN, AERASI DAN SUHU FERMENTOR TERHADAP KUALITAS BIJI KAKAO - Sri Hartuti; Nursigit Bintoro; Joko Nugroho Wahyu Karyadi; Yudi Pranoto (AGROINTEK, 2020)
Good postharvest handling must be done to get high-quality cocoa beans. This study aims to determine the effect and relationship of cocoa pod ripening time, aeration and fermentor temperature during fermentation on the pH and fermentation index, and to know the value of other quality parameters of cocoa beans, such as water content, ash content, protein content, fat content, carbohydrate content, color chroma, and hue. The results of the RSM analysis also showed that the cacao pod ripening time, aeration rate and fermenter temperature had different effects on the fermentation index and pH of the cocoa beans produced, which was indicated by the R² value for each parameter, 74.7% for the index fermentation and 56.5% for the pH of the cocoa beans. Based on the fermentation index value and the pH of the cocoa beans obtained, it was found that the ripening of the cocoa pods, aeration and the temperature of the fermentor provided were able to produce good quality fermented cocoa beans. The quality values of cocoa beans obtained include: fermentation index ≥ 1, pH of cocoa beans from 4.97 to 6.31, moisture content of  6.5 - 7.8%, ash content of 3.21 - 4.12%, chroma color value 16.50 - 25.28, hue color values 30.01 - 51.73, fat content 20.91 - 47.19%, protein content 10.45 - 16.47% and carbohydrate content 29.81-57.70 %.